Integration of Theory of Planned Behavior and Norm Activation Model on Student Behavior Model Using Cars for Traveling to Campus - Setiawan, R.; Santosa, W.; Sjafruddin, A. (Institute of Research and Community Outreach - Petra Christian University, 2014)
Although there are clear environmental, economic, and social drawbacks in using private vehicles, students still choose cars to get to campus. This study reports an investigation of psychological factors influencing this behavior from the perspective of the Theory of Planned Behavior and Norm Activation Model. Students from three different university campuses in Surabaya, Indonesia, (n = 312) completed a survey on their car commuting behavior. Results indicated that perceived behavioral control and personal norm were the strongest factors that influence behavioral intention. Attitude, subjective norm, perceived behavioral control, and personal norm explain 62.7% variance of the behavioral intention. In turn, behavioral intention explains 42.5% of the variance of the actual car use. Implications of these findings are that in order to alter the use of car, university should implement both structural and psychological interventions. Effective interventions should be designed to raise the awareness of negative aspects of car use.